A Rapid Review of the Impact of Gratitude on Suicide Risk Management - Efri Widianti; Nur Oktavia Hidayati; Yosalia Mahirah Salsabila; Rizki Amalia Nurfadhilah; Indra Kusumah (Jurnal Penelitian Perawat Profesional, 2025)
Suicide is a major global health problem, with significant psychological and social impacts. Gratitude therapy is a positive psychological intervention that improves mental well-being and may reduce suicide risk, and is comparable in effectiveness to cognitive behavioral therapy (CBT) in improving life satisfaction . The aim of this study was to evaluate the effectiveness of gratitude therapy in reducing suicide risk among individuals with mental health disorders. This study was conducted using a rapid review method of articles explaining the effectiveness of gratitude therapy in reducing the risk of suicide. This study involved a systematic literature search in databases such as PubMed , EBSCO, and ScienceDirect . The inclusion criteria for this study were articles published between 2015 and 2024, in English and Indonesian, with full-text availability, and focusing on gratitude therapy for mental health patients at risk of suicide. The screening followed the PRISMA guidelines, resulting in 9 articles for final analysis. A total of 9 relevant articles were reviewed. Four studies examined the application of gratitude therapy to psychosocial problems, while five studies focused on individuals with mental disorders. For psychosocial problems, gratitude interventions such as gratitude diaries and reflection journals were effective in reducing stress and increasing life satisfaction by 6.89%, increasing social connectedness, and fostering positive coping mechanisms. For mental health disorders, gratitude therapy showed a 5.8% benefit in reducing feelings of hopelessness, increasing optimism, and alleviating depressive symptoms. This study suggests that gratitude therapy serves as a promising intervention to reduce suicide risk and improve mental health across a range of settings and populations. However, these findings have several limitations and further research is needed to expand its applicability and efficacy.